Violence and Human Capital Investments - Koppensteiner, Martin Foureaux; Menezes, Lívia (Journal of Labor Economics, 2021)
We combine extremely granular information on the location and timing of homicides with a number of large administrative educational data sets from Brazil to estimate the effect of exposure to homicides around schools, around students’ residences, and on their way to school. We show that violence has a detrimental effect on both school attendance and standardized test scores and that it increases the dropout rates of students substantially. We use exceptionally rich information from student- and parent-background questionnaires to investigate the effect of violence on aspirations and attitudes toward education. We find that boys systematically report lower educational aspiration.